PENGARUH PENGUNGKAPAN CORPORATE SOCIAL RESPONSIBILITY TERHADAP RESPON NILAI PERUSAHAAN PADA SUBSEKTOR SEMEN, KERAMIK, PLASTIK, DAN KIMIA - Natanagara, Devina Mustikarina (Business Accounting Review, 2015)
The purpose of this study was to know whether there was significant affects of corporate social responsibility disclosure which was measured by using the global reporting initiative 3.1 towards the firm value which was measured by using the Tobinâs Q. The sample used in this study were 120 observations in subsectors of chemical, cement, ceramic, and plastic industry during the period of 2009-2013. The results of this study showed that Corporate Social Responsibility significantly affect the firm value. Market share as control variable had positive influence on firm value. While the Debt to Equity Ratio control variable had no affect on firm value and firm size control variable had negative influence on firm value.